An investigation on the antibacterial, cytotoxic, and antibiofilm efficacy of starch-stabilized silver nanoparticles - Mohanty, Soumitra; Mishra, Saswati; Jena, Prajna; Jacob, Biju; Sarkar, Biplab; Sonawane, Avinash (Nanomedicine, 2012)
The increased emergence of drug resistant microbes creates a major challenge to the scientific community for successful development of effective therapeutics. The antimicrobial activities of silver ions are well known, but limited information is available on the effects of green silver-nanoparticles (AgNPs) on human pathogens. In this article, we evaluated the antibacterial activity of starch-stabilized AgNPs against a panel of human pathogens commonly associated with air, water and food borne infections. The shape and size distribution of AgNPs were characterized by transmission electron microscopy. We showed that AgNPs were more effective against Gram-positive and Gram-negative pathogens as compared with acid-fast bacteria. AgNPs were not cytotoxic to macrophages at the bactericidal concentration and can augment intracellular killing potential of macrophages. Furthermore, we showed that AgNPs disrupt biofilm formation and exhibit better antibacterial activity compared to human cationic antimicrobial peptide LL-37. In summary, our data suggest AgNPs as a promising template for the design of novel antibacterial agents. In this fundamental study, the significance of starch-stabilized AgNP-s is studied as antimicrobial agents on a variety of human pathogens. AgNP-s are expected to become universally utilized agents in our efforts to prevent and fight infections. [Display omitted] Graphical representation of different activities of AgNPs against bacteria and macrophages. Starch-stabilized AgNPs exhibit antimicrobial activity, inhibit biofilm formation, no cytotoxic effect on mouse macrophages, and kill intracellular bacteria.